2020
DOI: 10.1111/jog.14320
|View full text |Cite
|
Sign up to set email alerts
|

A cut‐off value for systemic immune‐inflammation index in the prediction of adverse neonatal outcomes in preterm premature rupture of the membranes

Abstract: Aim To determine a cut‐off value for systemic immune‐inflammation index (SII)(neutrophil × platelet /lymphocyte) in the prediction of adverse neonatal outcomes in preterm premature rupture of the membranes (PPROM). Methods This retrospective cohort study was conducted among singleton pregnancies with PPROM. Cases were divided into two main groups: Group 1) PPROM diagnosed at 24th–28th weeks of gestation and Group 2) PPROM diagnosed at >28th–34th weeks of gestation. Thereafter, main study groups were divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 33 publications
1
45
0
Order By: Relevance
“…In a study in 1986, Müftüogľu et al showed signi cantly higher ESR and CRP results in patients with active BD rather than inactive or control group (20). This result was also supported by Tanacan et al study in 2020 which ESR and CRP levels in 103 active BD patients showed a statistically signi cant difference compared to 63 patients in the inactive disease group (29). Our study results also con rm this hypothesis since ESR and CRP values in 450 individuals with active BD showed considerable difference compared to 64 inactive BD patients.…”
Section: Discussionsupporting
confidence: 90%
“…In a study in 1986, Müftüogľu et al showed signi cantly higher ESR and CRP results in patients with active BD rather than inactive or control group (20). This result was also supported by Tanacan et al study in 2020 which ESR and CRP levels in 103 active BD patients showed a statistically signi cant difference compared to 63 patients in the inactive disease group (29). Our study results also con rm this hypothesis since ESR and CRP values in 450 individuals with active BD showed considerable difference compared to 64 inactive BD patients.…”
Section: Discussionsupporting
confidence: 90%
“…[7][8][9] The SII value was evaluated for prediction of adverse neonatal outcomes in preterm premature rupture of membranes (PPROM), and researchers found significantly increased SII values in the patients with PPROM. [10] Monochorionic twin pregnancies have higher perinatal complication risks than dichorionic twin pregnancies. [20] Riyami et al [21] observed that high perinatal morbidity and mortality rate is likely due to frequent twinto-twin transfusion syndrome, prematurity, fetal growth restriction, and intrauterine fetal death.…”
Section: Discussionmentioning
confidence: 99%
“…[7] It has been used as a clinical marker to predict the prognosis of the obstetric complications and oncological diseases in various studies. [8][9][10][11] In this study, we aim to evaluate the SII in twin pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Prediction and prevention of pregnancy complications such as preterm birth are significant issues in the modern obstetric field 33 . Determination of delivery time due to preterm birth is especially critical because the development of maternal and neonatal complications is complex, and researchers developed many methods to solve neonatal and maternal complications to date 34 . This article will help diagnose and predict preterm birth cases via the usage of the placental sonoelastography, a relatively new field of study, to investigate placental tissue structure.…”
Section: Discussionmentioning
confidence: 99%